Status and future thrust areas of rapeseed-mustard research in India - Kumar, Arvind; Chauhan, J S (The Indian Journal of Agricultural Sciences, 2005)
Rapeseed-mustard group of crops account for 21.6 and 23.2% of the total oilsced crop area and production, respectively, during 2003-04. Rajasthan, Uttar Pradesh, Haryana, Madhya Pradesh and West Bengal, together contribute 82.7 and 86.9% to the total national hectarage and production, respectively. The yield ranged from as low as 524 kg/ha in Assam to as high as 1559 kg/ha (Haryana) with overall yield of 1151 kg/ha in 2003-04. Irrigated area under these crops increased steadily from 51.3% in 1985-86 (launching of Technology Mission on Oilseeds) to 66% in 2000-01. A total of 6688 and 5162 accessions of rapeseed-mustard are available at the NRCRM and other AICRP-RM Centres, respectively. Systematic evaluation led to the identification of valuable donors for various diseases, quality parameters and agro-morphological characters. Experimental CMS based hybrids in Indian mustard and GMS based in yellow sarson are being evaluated in multi-location trials. One low erucic acid variety of Indian mustard ('Pusa Karishma') and two double low varieties of gobhi sarson ('GSC 5' and 'TEN Uttam Jawahar') have been released recently. In all, 163 varieties have been recommended/released from 1936 (RT 11) to 2005 (YRN 6) in India. Of these, 103 varieties have been notified for breeder seed production. Suitable cropping sequences and intercropping combinations with Indian mustard for different states have been identified. Integrated nutrient management strategy to increase fertilizer-use efficiency is being developed. Yield losses due to various diseases and insect pests of these crops in different states were assessed and management schedule for major diseases (Alternaria blight, white rust, Sclerotinia rot and powdery mildew) and insect pests (aphid, painted bug and sawfly) have been developed. In large number (3977) of frontline demonstrations conducted in 16 states during 1988-89 to 2004-05, the productivity improvement ranged between 17 and 212% (rainfed) and 10 and 131% (irrigated) with the use of improved package. The average yield increase with improved technologies over farmers' practice at the national level was 36%. Thus, additional 2 million tonnes production can be achieved by adopting the recent production and protection technologies. The present scenario of rapseed-mustard in India and future research needs have been discussed in this paper.